VD_FINDINFO Jug / 2023 / 350 vom 21. November 2022 - VD Tribunal cantonal (2022)
ADMISSION PARTIELLE, MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP, FAUTE, PLACEMENT PSYCHIATRIQUE, TRAITEMENT AMBULATOIRE | 22 ad 129 CP, 47 CP, 56 CP, 63 CP, 64 al. 1 CP